Adrenal secretion produced by asphixia - Houssay, Bernardo Alberto (1926)
Asphyxia produces a marked epinephrin discharge. This fact reported by several authors has been denied by others. Our present observations confirm the existence and give some insight into the cause of this phenomenon.